Tuning of Transport and Magnetic Properties in Epitaxial LaMnO3+δ Thin Films - J. Chen; L. Hu; W. J. Lu; B. Yuan; K. J. Zhang; J. M. Dai; Y. P. Sun (Advances in Condensed Matter Physics)
The effect of compressive strain on the transport and magnetic properties of epitaxial LaMnO3+δ thin films has been investigated. It is found that the transport and magnetic properties of the LaMnO3+δ thin films grown on the LaAlO3 substrates can be tuned by the compressive strain through varying film thickness. And the insulator-metal transition, charge/orbital ordering transition, and paramagnetic-ferromagnetic transition are suppressed by the compressive strain. Consequently, the related electronic and magnetic transition temperatures decrease with an increase in the compressive strain. The present results can be explained by the strain-controlled lattice deformation and the consequent orbital occupation. It indicates that the lattice degree of freedom is crucial for understanding the transport and magnetic properties of the strongly correlated LaMnO3+δ.